ANALYSIS OF TENTOR’S STRATEGIES IN IMPROVING STUDENTS ENGLISH SKILLS AT HARITH FOUNDATION COURSE INSTITUTION - Yunita Dafri; Jusriati Jusriati; Nasriandi Nasriandi (UNIVERSITAS SERAMBI MEKKAH, 2023)
The purpose of this study is to analyze the strategies used by tutors in teaching English at the Harith Foundation Course Institution. The subject of this research is an English tutor who teaches at the Harith Foundation Course Institution. The researcher uses Roy Killen's theory to analyze the strategies used by tutors in teaching English. Roy Killen's theory is a teaching strategy that consists of nine techniques, namely direct instruction, discussion, group work, cooperative learning, problem solving, research, role playing, case studies, and writing. This study used a qualitative method with an approach to descriptive analysis. Data was collected through observation, semi-structured interviews and observations of the Harith course institute tutors Foundation. The results of the research show that Learning techniques used by tutors in teaching English at Harith Foundation course institutions are Problem Based Learning, Project Based Learning and Cooperative Strategies and Techniques for assessing students' success in learning English by tutors at Harith Foundation course institutions are pretset and posttest.